2004
DOI: 10.1021/ic048814u
|View full text |Cite
|
Sign up to set email alerts
|

Unique Hydrogen Bonding Correlating with a Reduced Band Gap and Phase Transition in the Hybrid Perovskites (HO(CH2)2NH3)2PbX4 (X = I, Br)

Abstract: The first hybrid perovskites incorporating alcohol-based bifunctional ammonium cations, (HO(CH(2))(2)NH(3))(2)PbX(4) (X = I, Br), have been prepared and characterized. (HO(CH(2))(2)NH(3))(2)PbI(4) adopts a monoclinic cell, a = 8.935(1) A, b= 9.056(2) A, c = 10.214(3) A, beta = 100.26(1) degrees , V = 813.3(3) A(3), P2(1)/a, and Z = 2, and (HO(CH(2))(2)NH(3))(2)PbBr(4) is orthorhombic, a = 8.4625(6) A, b = 8.647(1) A, c = 19.918(2) A, V = 1457.5(2) A(3), Pbcn, and Z = 4. In the layered structures, a unique hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 25 publications
7
112
1
Order By: Relevance
“…The layered perovskite hybrid structures provide a good platform for the preparation and investigation of two-dimensional (2D) quantum well systems (89)(90)(91)(92). A number of interesting optical, electrical, and magnetic properties have been discovered in these materials (75,90,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108).…”
Section: Crystalline Inorganic-organic Hybrid Materialsmentioning
confidence: 99%
“…The layered perovskite hybrid structures provide a good platform for the preparation and investigation of two-dimensional (2D) quantum well systems (89)(90)(91)(92). A number of interesting optical, electrical, and magnetic properties have been discovered in these materials (75,90,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108).…”
Section: Crystalline Inorganic-organic Hybrid Materialsmentioning
confidence: 99%
“…This is made possible because of the incorporation of selected cations that are able to impact the bonding features of the inorganic framework. [5] Hybrids with enhanced structural dimensionality have also been considered. [6,7] In particular, we recently showed that in [Cu{O 2 C-(CH 2 ) 3 -NH 3 } 2 ]PbBr 4 the amino carboxylic acid zwitterionic molecules led both to the stabilization of a layered hybrid perovskite and to the formation of a Br-Cu-Cu-Br covalent bond pathway between adjacent perovskite layers.…”
Section: Introductionmentioning
confidence: 99%
“…Although Pb is a neighboring element of Bi with similar cation size and octahedral coordination character [13,19], their different oxidation states endow them with specific structural buildings and functional features. Typically, thermochromism as an interesting phenomenon has attracted much attention in the field of iodobismuthate or iodoplumbate hybrids [8,12,[20][21][22][23][24][25][26][27]. Differing from the thermochromic iodobismuthates, only a handful of thermochromic layered perovskite-type iodoplumbates [22][23][24][25][26][27] and two thermochromic heterometallic iodoplumbates ([Co(phen) 3 ] 2 [Pb 3 Cu 6 I 16 ] Á C 2 H 5 OH [12] and [Pb 3 I 10 Cu 4 (phen) 2 ] n ) [8] have been reported, which is likely due to their larger energy gap and limited response of their structures to the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, thermochromism as an interesting phenomenon has attracted much attention in the field of iodobismuthate or iodoplumbate hybrids [8,12,[20][21][22][23][24][25][26][27]. Differing from the thermochromic iodobismuthates, only a handful of thermochromic layered perovskite-type iodoplumbates [22][23][24][25][26][27] and two thermochromic heterometallic iodoplumbates ([Co(phen) 3 ] 2 [Pb 3 Cu 6 I 16 ] Á C 2 H 5 OH [12] and [Pb 3 I 10 Cu 4 (phen) 2 ] n ) [8] have been reported, which is likely due to their larger energy gap and limited response of their structures to the temperature. Although some explanations have been suggested for the above phenomenon, such as the temperature induced phase transition and lattice contraction, this kind of thermochromic property can generally be attributed to the distortion of iodoplumbate framework and consequent changes of absorption position and intensity, which implies the decisive roles of chain-like organic amines and heterometallic components.…”
Section: Introductionmentioning
confidence: 99%